Homegrown Muslim Extremism in the Netherlands: An Exploratory Note - Maria M. Komen (Journal of Strategic Security, 2014)
In his Widening Circles of Disidentification the Dutch sociologist Abram de Swaan argues that enmity and violent conflicts occur most frequently among groups that resemble one another, in transitional phases in which the social differences between these groups are growing smaller. This paper sets out to explore this thesis, in relation to the recent tensions in the Netherlands generated by a trend towards radicalization among second-generation Moroccan youth. Another relevant point that is discussed is the way some ethnic minority juveniles are socialised and integrated in Dutch society. Political radicalism among young Moroccans in the Netherlands seems to be promoted by emancipation and coercive family processes.